Photographic Capture-Recapture Analysis Reveals a Large Population of Indo-Pacific Bottlenose Dolphins (Tursiops aduncus) With Low Site Fidelity off the North West Cape, Western Australia - Haughey, Rebecca; Hunt, Tim; Hanf, Daniella; Rankin, Robert William; Parra, Guido J. (Frontiers in Marine Science, 2020)
Little is known about the ecology of Indo-Pacific bottlenose dolphins (Tursiops aduncus) inhabiting the coastal waters of tropical north-western Australia. We used photoidentification data collected between 2013 and 2015, site fidelity indexes and capturerecapture models to estimate the abundance and site fidelity patterns of Indo-Pacific bottlenose dolphins (T. aduncus) inhabiting the coastal waters off the North West Cape (NWC), Western Australia. A standardized site fidelity index (SSFI) indicated low site fidelity (SSFI = 0.019) at the population level to the 130 km2 study area. Agglomerative hierarchical clustering (AHC) of individual re-sight rates classified 58% of individuals as “transients.” Open POPAN modeling estimated a super-population size of 311 (95% CI: 249–373) individuals over the study period. A maximum likelihood transient model which considers both resident and non-resident individuals in a population, estimated a resident population of 141 (95% CI: 121–161) individuals and a super-population of 370 (95% CI: 333–407) individuals. These models indicate that a large population of Indo- Pacific bottlenose dolphins of relatively high density (an average of 2.4–2.8 bottlenose dolphins per km2) inhabits the waters off the NWC. The large number of both resident and non-resident bottlenose dolphins found throughout the coastal waters off the NWC suggest this area, as well as neighboring waters outside our study area, are of high importance to this species.